Predictors of Length of Stay in the Pediatric Intensive Care Unit at Palembang BARI Regional General Hospital - Ahmad Bayu Alfarizi (MESINA (Medical Scientific Journal), 2026)
Paediatric intensive care unit (PICU) care is resource intensive, and length of stay (LOS) is widely used to reflect bed utilization and care complexity. This study aimed to identify factors associated with LOS >3 days among PICU patients at Palembang Bari General Hospital. We conducted a retrospective observational study using the PICU admission database from January 1, 2019 to December 31, 2025. Variables included age, sex, primary diagnosis category, Glasgow Coma Scale (GCS), white blood cell count, and platelet count. The outcome was LOS >3 days. Multivariable logistic regression was performed. Among 1,034 admissions, median age was 6 months (IQR 2–12 months) and 58.8% were male. Median LOS was 3 days (IQR 2–4) and 30.7% had LOS >3 days. The most frequent diagnosis categories were respiratory (28.1%), neurologic (19.8%), and dengue (13.1%). In the multivariable model (n=716), neurologic diagnosis was associated with LOS >3 days versus respiratory diagnoses (OR 1.58; 95% CI 1.01–2.47), and GCS ?8 increased the odds of LOS >3 days (OR 2.67; 95% CI 1.33–5.36). Non-dengue shock was associated with lower odds of LOS >3 days and should be interpreted cautiously (OR 0.39; 95% CI 0.20–0.78). In conclusion, neurologic involvement at admission (neurologic diagnosis and low GCS) is a key marker of prolonged PICU stay in this setting.